Do children who receive an ‘early dose’ of MMR vaccine during a measles outbreak return for their regularly scheduled dose? A retrospective population-based study - Guo, Xiaoyan (BMJ Open, 2016)
BACKGROUND: Children under the age of 12 months may receive an early dose of measles–mumps–rubella (MMR) vaccine to provide short-term protection in the case of a disease outbreak. Following a measles outbreak in Alberta, Canada, there was concern that children who received an early dose may not be returning for their routinely scheduled dose at 12 months, leaving them vulnerable to disease in the long term. METHODS: This population-based study of children born between 2006 and 2014 used administrative health data to assess coverage and timeliness of the first routine dose of MMR vaccine administered at age 12–24 months for children who received an early dose of the vaccine due to a disease outbreak. We compared this group to children who received an early dose due to travel to a measles-endemic region and to children who did not receive an early dose. RESULTS: Only 5.5% of 366 351 children received an early dose. Coverage for the routine dose at age 24 months was 96.5% for children receiving an outbreak dose, 92.2% for those travelling to measles-endemic regions and 86.6% for those without an early dose (p<0.0001). The multivariable Cox proportional hazard analysis, controlling for neighbourhood income, place of residence and interaction effects, determined that, as compared to the general cohort, the outbreak group was most likely to obtain the first routine dose (adjusted HR (aHR): 1.52, 95% CI 1.44 to 1.60), followed by the travel group (aHR: 1.26, 95% CI 1.18 to 1.34). CONCLUSIONS: It is reassuring that the majority of children who received an early dose returned for their routine dose and did so in a timely manner.